The tale of briar bank eaudiobook Cottage tales of beatrix potter series, book 5. - Albert, Susan Wittig (Cottage Tales of Beatrix Potter, 2010)
In this fifth delightful entry, Anthony and Agatha Award nominee Susan Wittig Albert re-imagines Beatrix Potter wearing her sleuthing cap as the village of Sawrey lies buried beneath a blanket of Christmas snow. While she and her animal friends investigate a puzzling death, Miss Potter wonders if she can acknowledge her fondness for Mr. Heelis and still remain loyal to her fiancE's memory.